Biological study of Rastrelliger brachysoma (Van Kampen) in the west coast of Peninsular Malaysia - Mansor Mat Isa (Ministry of Agriculture, Department of Fisheries, 2013)
The purpose of this study is to gather information for rational fisheries management or may add to the knowledge and life history of the species. Biological data were collected from various landing places in the West Coast of Peninsular Malaysia. The data were analysed to determine the length-weight relationship, growth parameters, mortality and recruitment pattern, maturity studies and length at first maturity